Lipid screening: is it enough to measure total cholesterol concentration?. Issue 6752 (22nd September 1990) - Neil, H A; Mant, D; Jones, L; Morgan, B; Mann, J I
Abstract : OBJECTIVES–To determine whether measurement of total cholesterol concentration is sufficient to identify most patients at lipoprotein mediated risk of coronary heart disease without measurement of triglyceride and high density lipoprotein (HDL) cholesterol concentrations. DESIGN–Cross sectional screening programme. SETTING–Six general practices in Oxfordshire. PATIENTS–1901 Men and 2068 women aged 25-59. MAIN OUTCOME MEASURE–Cardiovascular risk as assessed by fasting venous plasma concentrations of total cholesterol, triglyceride, and HDL cholesterol. RESULTS–2931 Patients (74% of those screened) had a total cholesterol concentration of less than 6.5 mmol/l. If the triglyceride concentration had not been measured in these patients isolated hypertriglyceridaemia (greater than or equal to 2.3 mmol/l) would have remained undetected in 185. Among these 185 patients, however, 123 were overweight or obese and only 18 (0.6% of those screened) had an increased risk associated with both a raised triglyceride concentration (greater than or equal to 2.3 mmol/l) and a low HDL cholesterol concentration (less than 0.9 mmol/l). Conversely, in the 790 patients with predominant hypercholesterolaemia (cholesterol concentration greater than or equal to 6.5 mmol/l and triglyceride concentration less than 2.3 mmol/l) measurement of HDL cholesterol concentration showed that 348 (9% of those screened) had only a moderately increased risk with a ratio of total to HDL cholesterol of less than 4.5 and 104 had a low risk with a ratio of less than 3.5. CONCLUSIONS–Fasting triglyceride and HDL cholesterol concentrations identify few patients at increased risk of coronary heart disease if the total cholesterol concentration is less than 6.5 mmol/l. HDL cholesterol and triglyceride concentrations should, however, be measured in patients with a total cholesterol concentration exceeding this value. Total cholesterol concentration alone may overestimate risk in a considerable number of these patients, and measurement of HDL cholesterol concentration allows a more precise estimate of risk. Measurement of the triglyceride concentration is required to characterise the lipoprotein abnormality. A patient should not be started on a drug that lowers lipid concentrations without having had a full lipoprotein assessment including measurement of HDL cholesterol concentration.